The Influence of Creative Economy-Based Entrepreneurial Cognitive on Entrepreneurial Success - Alni Dahlena; Galih Abdul Fatah Maulani; Nizar Alam Hamdani; Asri Solihat (Entrepreneurship Faculty, Universitas Garut, 2025)
Basically, the concept of entrepreneurship includes an individual's ability to recognize opportunities, overcome challenges, and adapt to rapid change. Cognitive entrepreneurship is closely related to entrepreneurship education which is aimed at improving creative and critical thinking skills. The aim of this study is to analyze the influence between creative economic variables and entrepreneurial cognition in encouraging entrepreneurial success. The research method uses a cross-sectional survey approach. This approach was chosen to obtain data from respondents at a certain time. Data collection techniques using questionnaires. Data analysis was performed using SmartPLS software. Descriptive analysis was conducted to provide a general overview of the respondents. Furthermore, multiple regression analysis (SEM) was conducted. The results of this study identified that the creative economy variable towards entrepreneurial success had a coefficient of 0.140, while the entrepreneurial cognitive variable towards entrepreneurial success had a coefficient of 0.652. It was identified that the combination of creative economy and entrepreneurial cognitive factors was able to explain approximately 52.7% of the variation in entrepreneurial success. The results of the analysis of these coefficient values were relatively low to moderate, so their influence was not too dominant. The bootstrapping results showed a coefficient value of 0.000, which means the influence of entrepreneurial cognition on entrepreneurial success was not significant. Therefore, the influence of creative economy-based entrepreneurial cognition on entrepreneurial success is a complex interaction in developing benchmarks for entrepreneurial success.